Accident analysis based on systems thinking approach: Case study of "6·13" tank truck explosion in Wenling, China. Issue 3 (21st June 2022) - Yang, Peng; Zhang, Lijing; Tao, Gang
Abstract: The problem China is currently facing is why accidents related to the road transportation of hazardous chemicals, with the same or similar causes, keep happening and why we do not seem able to learn from these events. Systems thinking is a discipline of seeing systems holistically, and it creates a clearer picture of the dynamic, systematic structures that have contributed to the occurrence of a major incident. The "6·13" tank truck explosion accident is considered to be the most serious accident in the development of the Chinese road transportation system of hazardous chemicals in the past 5 years. From the accident investigation report, the system elements were identified, and a causal loop diagram was developed based on the systems thinking archetype of "shifting the burden." In this paper, we focused on two problem symptoms: "defective construction of anti‐collision guardrails" and the "unsafe behavior of speeding." The causal loop diagram not only illustrated symptomatic solutions to the problem symptoms in the accident report, but also identified fundamental solutions. Most importantly, this research revealed how an underlying systemic structure ultimately resulted in a major accident. This knowledge is useful for developing prevention policies and industrial strategies and benefits the safety and sustainability of China's chemical industries.